2011
DOI: 10.5194/acp-11-275-2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of simulated photochemical partitioning of oxidized nitrogen in the upper troposphere

Abstract: Abstract. Regional and global chemical transport models underpredict NO x (NO + NO 2 ) in the upper troposphere where it is a precursor to the greenhouse gas ozone. The NO x bias has been shown in model evaluations using aircraft data and total column NO 2 (molecules cm −2 ) from satellite observations (Napelenok et al., 2008). The causes of NO x underpredictions have yet to be fully understood due to the interconnected nature of simulated emission, transport, and chemistry processes. Recent observationbased … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…The model framework used here was originally developed by Henderson et al (2011); the core framework and additions for this work are described below. The model framework relies on the convective turnover of the upper troposphere, or deep convection, that maintains a "persistent imbalance" (Prather and Jacob, 1997).…”
Section: Model Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The model framework used here was originally developed by Henderson et al (2011); the core framework and additions for this work are described below. The model framework relies on the convective turnover of the upper troposphere, or deep convection, that maintains a "persistent imbalance" (Prather and Jacob, 1997).…”
Section: Model Frameworkmentioning
confidence: 99%
“…Photochemical processing includes gas-phase chemistry, partitioning to aerosols, and heterogeneous reactions. The gas-phase chemistry is simulated using the deterministic model used by GEOS-Chem "full" NO x -hydrocarbon simulations (Mao et al, 2009) with the improvements suggested by Henderson et al (2011). Additional reactions for CH 3 O 2 NO 2 have been added based on JPL11 with photolysis estimated using HNO 4 as a proxy (following Browne et al, 2011).…”
Section: Photochemical Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Aircraft campaigns during the summers of 2004 and 2013, including the International Consortium for Atmospheric Research on Transport and Transformation (ICARTT; Singh et al, 2006), the Southeast Nexus (SENEX; Warneke et al, 2016), and the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS; Toon et al, 2016), provide detailed characterization of tropospheric composition in this region separated by nearly a decade. These data have been widely used to evaluate model estimates of RON and ozone Pierce et al, 2007;Perring et al, 2009;Fischer et al, 2014;Hudman et al, 2007;Henderson et al, 2011;Hudman et al, 2009;Edwards et al, 2017;Baker and Woody, 2017;Travis et al, 2016;Mao et al, 2013b;Fisher et al, 2016;Yu et al, 2016;Liu et al, 2016). Together with measurements from surface networks, including the National Atmospheric Deposition Program (NADP) and EPA Air Quality System (AQS), these datasets enable a close examination of responses of RON and surface ozone to NO x emission reductions in this region.…”
Section: Introductionmentioning
confidence: 99%